Effects of supplemental potassium on growth, nutritional status and antioxidant defense system of wheat (Triticum durum L.) under salt stress - Faouzi HORCHANI; Arij BOUAZZI; Amal BOUALLEGUE; Zouhaier ABBES (Notulae Scientia Biologicae)
Potassium (K+) is an essential macronutrient playing a crucial role in plant growth and development as well as in many physiological and biochemical processes. An adequate K+ concentration in the rooting medium has been linked to plant’s tolerance to abiotic stress.  This study was undertaken to assess the effects of different K+ concentration treatments (0.2, 2.5 and 5 mM) on the growth, nutritional behavior, total chlorophyll, proline and malondialdehyde contents as well as total polyphenols and ascorbate contents, and superoxide dismutase and catalase activities of durum wheat seedlings under salt stress (100 mM NaCl). Obtained results showed that increasing the K+ availability in the nutrient solution enhanced wheat seedlings’ growth-related parameters, namely relative growth rate and relative water content. Concomitantly, the chlorophyll pigment and proline contents were significantly increased, whereas the level of lipid peroxidation was noticeably decreased. Simultaneously, the antioxidant defense machinery was induced through the significant increases in total polyphenols and ascorbate contents as well as in the activities of superoxide dismutase and catalase enzymes. Taken together, the results of the current study showed that K+ plays a key role in the mitigation of the devastating effects of salt stress on durum wheat’s growth. Therefore, increasing the K+ availability in the rooting medium may be used as an efficient method for wheat cultivation in salt-affected soils.